An Updated Software Almanac. - Armour, Phillip G. (Communications of the ACM, 2015)
The article focuses on the business of software as examined in the 2014 Research Edition of the "QSM Software Almanac" published by Quantitative Software Management (QSM). Topics discussed include the core metrics that provide insights into the health of software projects and organizations, some industry trends over time such as project duration, the decline of project effort along with the delivered size of systems, and the median project team size, and some useful approaches for the measurement of projects as described in the Almanac.